A Study on the Impact of Poly(3-hexylthiophene) Chain Length and Other Applied Side-Chains on the NO(2) Sensing Properties of Conducting Graft Copolymers - Procek, Marcin (Sensors (Basel), 2018)
The detection and concentration measurements of low concentrations of nitrogen dioxide (NO(2)) are important because of its negative effects on human health and its application in many fields of industry and safety systems. In our approach, conducting graft copolymers based on the poly(3-hexylthiophene) (P3HT) conducting polymer and other side-chains, polyethylene glycol (PEG) and dodec-1-en, grafted on a poly(methylhydrosiloxane) backbone, were investigated. The grafts containing PEG (PEGSil) and dodec-1-en (DodecSil) in two variants, namely, fractions with shorter (hexane fraction -H) and longer (chloroform fraction -CH) side-chains of P3HT, were tested as receptor structures in NO(2) gas sensors. Their responses to NO(2), within the concentration range of 1–20 ppm, were investigated in an nitrogen atmosphere at different operating temperatures—room temperature (RT) = 25 °C, 50 °C, and 100 °C. The results indicated that both of the copolymers with PEG side-chains had higher responses to NO(2) than the materials with dodec-1-en side-chains. Furthermore, the results indicated that, in both cases, H fractions were more sensitive than CH fractions. The highest response to 1 ppm of NO(2,) from the investigated graft copolymers, had PEGSil H, which indicated a response of 1330% at RT and 1980% at 100 °C. The calculated lower-limit of the detection of this material is lower than 300 ppb of NO(2) at 100 °C. This research indicated that graft copolymers of P3HT had great potential for low temperature NO(2) sensing, and that the proper choice of other side-chains in graft copolymers can improve their gas sensing properties.